2018
DOI: 10.1111/jfbc.12554
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of body weight, body fat mass, and serum leptin levels by addition of new beverage in normal diet of obese subjects

Abstract: Vinegar and garlic are well‐known functional foods used in reducing obesity, Hence, a new beverage was developed from dates vinegar and garlic juice in order to reduce obesity. Current investigation focused on 85 obese adults. Participants consumed 500 mL of either beverage or placebo daily into their normal diet for a period of 10 weeks. Body weight, body mass index (BMI), waist circumference, visceral fat area (VFA), serum lipid profile, serum leptin, alanine transaminase (ALT), aspirate transaminase (AST), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Presently, consumer concern in healthy food is on the rise due to the advancement in the field of functional foods formulation. Moreover, consumers are demanding value‐added foodstuff with new attributes and this has led to several studies with the aim of optimizing health benefits of food products (Ali, Ma, Rashid, Ayim, & Wali, ; Ubeda et al, ). Various researchers have reported the association among the ingestion of vegetables and fruits in reducing the risk of cancer, cardiovascular disease, inflammation, and metabolic syndrome‐related complications (Hung et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Presently, consumer concern in healthy food is on the rise due to the advancement in the field of functional foods formulation. Moreover, consumers are demanding value‐added foodstuff with new attributes and this has led to several studies with the aim of optimizing health benefits of food products (Ali, Ma, Rashid, Ayim, & Wali, ; Ubeda et al, ). Various researchers have reported the association among the ingestion of vegetables and fruits in reducing the risk of cancer, cardiovascular disease, inflammation, and metabolic syndrome‐related complications (Hung et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Dates contain fiber vital mineral (iron, selenium fluorine, and calcium) and vitamins (Vayalil, ). Results have shown that extracts from dates have exposed free radical scavenging activity, immunomodulatory, and antimutagenic activities, (Allaith, ; Khan, Sarwar, Wahab, & Haleem, ) and dates have cardioprotective, anti‐inflammatory, antiobesity, and antihypertensive effects (Ali, Ma, Ayim, & Wali, ; Ali, Ma, Rashid, et al, ). In the past, dates' vinegar did not receive the attention it deserves due to limited literature about the fruit.…”
Section: Introductionmentioning
confidence: 99%
“…Since the animals’ percentage of adipose tissue was similar among all groups (Figure 3), it can be suggested that any changes on these hormones were due to direct effects of the diets’ macronutrient composition and/or phenolic supplementation. In obese adults, PCs from dates and vinegar were shown to increase serum leptin concentration, when consuming them in a beverage during a ten‐week period (Ali et al., 2018). Montalbano et al.…”
Section: Resultsmentioning
confidence: 99%